CURRENT TRENDS IN THE TEACHING OF DRAWING IN EDUCATIONAL INSTITUTIONS IN NORTHERN IRELAND - Мелентьєв, Ярослав (SWorldJournal, 2025)
The article examines the features of teaching technical drawing in secondary and higher education institutions in Northern Ireland. Innovative methods are considered, such as the use of CAD, 3D printing, project-based learning, and the integration of draw